Strategi Manajemen Pendidikan Al-Qur’an dalam Mengembangkan Kepribadian Anak - Tomi; Yusuf Atma Suryabudi; Handaru Baskara Aji; Nafi'ah, Miftakhul Ngulumun; Sari, Putri Maya; Zahiduzzaka , Muhammad Faza; Sumedi (Program Studi Manajemen Pendidikan Islam UIN Sunan Ampel Surabaya, 2026)
Nowadays, many children are found with deviant characters towards morals and morals. Moral and moral degradation in children is mostly found at the age of entering adolescence or elementary school age. A child's education can be obtained because of the support and facilities provided by his parents. Since childhood, children must be accustomed to doing good activities. Educating, training, and guiding children slowly are things that must be applied to children in order to achieve good character and skills. The purpose of this study is to describe the application of Qur'anic education management in PPPA Raudhotul Jannah and its influence on children's personality development. Data collection techniques were carried out by means of observation, interviews, and documentation. After the data is collected, the data is then analysed based on the Miles and Huberman model analysis technique. The strategies used by the asatidz to instil Islamic children's personality character through various habituation such as, the strategy of delivering asatidz material to their students, the strategy of fostering asatidz to santri guardians which is carried out every month through meetings and recitation of santri guardians, and the strategy of fostering students in receiving the knowledge given. Various religious activities are implemented through amaliyah worship activities, habituation of congregational prayer and dhikr after prayer, and santri programmes. Religious education in PPPA Raudhatul Jannah has a significant positive impact on children's character.